Local urbanization impacts sandy beach macrofauna communities over time - Augusto, Matheus; Abude, Rayane R. S.; Cardoso, Ricardo S.; Cabrini, Tatiana M. B. (Frontiers in Marine Science, 2023)
Sandy beaches are ecologically important, physically dynamic, and heterogeneous habitats intrinsically related to human culture. However, these interactions present challenges for sandy beaches in the Anthropocene as stressors from urbanization increase. This study investigated sandy beach community responses to local urbanization in two periods. Beaches were classified into three urbanization categories: conserved (C), modified (M), and urbanized (U), and compared temporally (1997/1998 – first period; 2012 – second period). We hypothesized that community structure descriptors (total abundance, biomass, and richness) and bioindicator abundance (Emerita brasiliensis and Atlantorchestoidea brasiliensis) decreased temporally and be lower in urbanized beaches. The results partially corroborate the main hypothesis since there were different temporal responses from biological variables between each urbanization category (C, M, and U). The data supported that community structure descriptors decreased as local urbanization increased between categories (C, M, and U). Conserved beaches (C) presented higher values for community descriptors, and populations of E. brasiliensis and A. brasiliensis were more abundant compared to other groups (M and U). Modified beaches (M) presented resilience to local urbanization pressures since they are recently urbanized habitats, and some beaches are inside protected areas. The urbanized beaches (U) were impacted by the long-term pressures of urbanization and recreation, and community descriptors and bioindicators presented the lowest values in both periods. Species undergoing direct development, such as A. brasiliensis, should preferably be used as indicators of temporal changes due to local urbanization on sandy beaches, rather than indirect developers like E. brasiliensis. Identifying suitable indicators for long-term anthropogenic impacts from increasing urbanization is necessary for protecting sandy beach ecology.